HW2 - Probability Theory and Statistics (EE/TE 3341)...

Info iconThis preview shows pages 1–3. Sign up to view the full content.

View Full Document Right Arrow Icon

Info iconThis preview has intentionally blurred sections. Sign up to view the full version.

View Full DocumentRight Arrow Icon
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: Probability Theory and Statistics (EE/TE 3341) Homework 2 Solutions Problem Solutions : Yates and Goodman, 1.6.3 1.6.7 1.7.1 1.7.3 1.8.1 1.8.2 1.8.7 1.9.1 1.9.5 1.10.1 and 1.10.4 Problem 1.6.3 Solution (a) Since A and B are disjoint, P [ A ∩ B ] = 0. Since P [ A ∩ B ] = 0, P [ A ∪ B ] = P [ A ] + P [ B ] − P [ A ∩ B ] = 3 / 8 . (1) A Venn diagram should convince you that A ⊂ B c so that A ∩ B c = A . This implies P [ A ∩ B c ] = P [ A ] = 1 / 4 . (2) It also follows that P [ A ∪ B c ] = P [ B c ] = 1 − 1 / 8 = 7 / 8. (b) Events A and B are dependent since P [ AB ] negationslash = P [ A ] P [ B ]. (c) Since C and D are independent, P [ C ∩ D ] = P [ C ] P [ D ] = 15 / 64 . (3) The next few items are a little trickier. From Venn diagrams, we see P [ C ∩ D c ] = P [ C ] − P [ C ∩ D ] = 5 / 8 − 15 / 64 = 25 / 64 . (4) It follows that P [ C ∪ D c ] = P [ C ] + P [ D c ] − P [ C ∩ D c ] (5) = 5 / 8 + (1 − 3 / 8) − 25 / 64 = 55 / 64 . (6) Using DeMorgan’s law, we have P [ C c ∩ D c ] = P [( C ∪ D ) c ] = 1 − P [ C ∪ D ] = 15 / 64 . (7) (d) Since P [ C c D c ] = P [ C c ] P [ D c ], C c and D c are independent. Problem 1.6.7 Solution (a) For any events A and B , we can write the law of total probability in the form of P [ A ] = P [ AB ] + P [ AB c ] . (1) Since A and B are independent, P [ AB ] = P [ A ] P [ B ]. This implies P [ AB c ] = P [ A ] − P [ A ] P [ B ] = P [ A ](1 − P [ B ]) = P [ A ] P [ B c ] . (2) Thus A and B c are independent. 1 (b) Proving that A c and B are independent is not really necessary. Since A and B are arbitrary labels, it is really the same claim as in part (a). That is, simply reversing the labels of A and B proves the claim. Alternatively, one can construct exactly the same proof as in part (a) with the labels A and B reversed. (c) To prove that A c and B c are independent, we apply the result of part (a) to the sets A and B c . Since we know from part (a) that A and B c are independent, part (b) says that A c and B c are independent. Problem 1.7.1 Solution A sequential sample space for this experiment is a24 a24 a24 a24 a24 a24 H 1 1 / 4 a88 a88 a88 a88 a88 a88 T 1 3 / 4 a24 a24 a24 a24 a24 a24 H 2 1 / 4 T 2 3 / 4 H 2 1 / 4 a88 a88 a88 a88 a88 a88 T 2 3 / 4 • H 1 H 2 1 / 16 • H 1 T 2 3 / 16 • T 1 H 2 3 / 16 • T 1 T 2 9 / 16 (a) From the tree, we observe P [ H 2 ] = P [ H 1 H 2 ] + P [ T 1 H 2 ] = 1 / 4 . (1) This implies P [ H 1 | H 2 ] = P [ H 1 H 2 ] P [ H 2 ] = 1 / 16 1 / 4 = 1 / 4 . (2) (b) The probability that the first flip is heads and the second flip is tails is P [ H 1 T 2 ] = 3 / 16....
View Full Document

This note was uploaded on 01/30/2012 for the course CS 3341 taught by Professor Baron during the Fall '08 term at University of Texas at Dallas, Richardson.

Page1 / 7

HW2 - Probability Theory and Statistics (EE/TE 3341)...

This preview shows document pages 1 - 3. Sign up to view the full document.

View Full Document Right Arrow Icon
Ask a homework question - tutors are online